EFFICIENCYANALYSIS OF COST COMPARE TO ASSETS ON SHARIA BANKWITH OFFICE CHANNELING - Kusumaningsih, Ani; Juanda, Gustian; Marjohan, Masno (EAJ (Economic and Accounting Journal), 2018)
Efficiency is a theoretically parameter that can be used to measure the bank performance. This research aims to find out the factors that can cause the efficiency value difference of Sharia Bank (Unit Usaha Syariah/UUS) in Indonesia, especially which have the office channeling facility. The research data is monetary data of Sharia Bank excludeBPD (Bank Pembangunan Daerah/Local Development Bank). It was obtained from Bank of Indonesia. Then, it was divided into input and output variables. The determination of input output variables at this research uses parametric approach, Stochastic Frontier Approach (SFA). Its input output variables consist of Total Loan, Total Effect, Labor Cost, Interest Cost, Total Cost and compare to Total Asset. The methods used in this study are measured in percentage. Closer to 100% means a bank acts more efficient. In each period (2011-2015), there are efficiency score, which is resulted by comparing one bank to others in sample. It implies that one bank acts as the most efficient bank in each year relatively to others. The efficiency score for the most efficient bank is 100%.The result of the analysis shows the mean of score for all of bank (UUS exclude BPD) is more than 99% which is nearly 100%. And the highest score is Bank OCBC NISP Tbk.